PREVALENCE OF PROBLEMATIC INSTAGRAM USE AND PSYCHOLOGICAL DISTRESS AMONG COLLEGE STUDENTS - V. Sathishanandan; M. Saravanan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Visual communication has become an integral part of our daily lives, with social media platforms like Instagram playing a significant role in shaping our online interactions. With over 1.2 billion active users, Instagram has become a vital tool for socializing, self-expression, and entertainment (Statista, 2024). While Instagram offers numerous benefits, such as staying connected with friends and family, sharing experiences, and accessing information, excessive and problematic use can lead to negative consequences, including decreased self-esteem, depression, and anxiety (Király et al., 2019; Lin et al., 2020).